2019
DOI: 10.3390/molecules24234387
|View full text |Cite
|
Sign up to set email alerts
|

Stacks of Azobenzene Stars: Self-Assembly Scenario and Stabilising Forces Quantified in Computer Modelling

Abstract: In this paper, the columnar supramolecular aggregates of photosensitive star-shaped azobenzenes with benzene-1,3,5-tricarboxamide core and azobenzene arms are analyzed theoretically by applying a combination of computer simulation techniques. Without a light stimulus, the azobenzene arms adopt the trans-state and build one-dimensional columns of stacked molecules during the first stage of the noncovalent association. These columnar aggregates represent the structural elements of more complex experimentally obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 77 publications
(196 reference statements)
0
8
0
3
Order By: Relevance
“…В литературе существует множество вычислительных подходов к описанию азобензолов или азо-содержащих соединений, привитых к различным поверхностям. В наших предыдущих исследованиях использовались теоретические и вычислительные методы в диапазоне от ab initio и атомистической молекулярной динамики до крупнозернистого моделирования и термодинамической теории [16][17][18][19][20][21]. Цель настоящего исследованияпредсказать, как конфигурационные перестройки и молекулярный дизайн влияют на структурные, электронные и транспортные свойства молекулярных переключателей и их комплексов с кластером золота, имитирующем кончик зонда.…”
Section: методика расчетовunclassified
See 1 more Smart Citation
“…В литературе существует множество вычислительных подходов к описанию азобензолов или азо-содержащих соединений, привитых к различным поверхностям. В наших предыдущих исследованиях использовались теоретические и вычислительные методы в диапазоне от ab initio и атомистической молекулярной динамики до крупнозернистого моделирования и термодинамической теории [16][17][18][19][20][21]. Цель настоящего исследованияпредсказать, как конфигурационные перестройки и молекулярный дизайн влияют на структурные, электронные и транспортные свойства молекулярных переключателей и их комплексов с кластером золота, имитирующем кончик зонда.…”
Section: методика расчетовunclassified
“…Необходимо подчеркнуть, что в предыдущих работах по моделированию бт-азо авторы приводят, вопервых, различные, а во-вторых, завышенные значения дипольных моментов: например, Lenfant и др. [10] получили µцис=4.9 и µтранс=1.8D (B3LYP/6-31G), и тот же авторский коллектив [13] Торсионные углы, характеризующие взаимную ориентацию бензольных колец в азо, незначительно отличаются от величин для транс-и цис-изомеров азобензола и различных замещенных азобензолов [17][18][19][20]. Нами подтверждается копланарность колец для транс-изомера, а также значения около 10º для цис-формы обоих переключателей.…”
Section: результаты расчетов и их обсуждениеunclassified
“…Cho et al developed a multiscale analysis framework based on coarse-grained MD simulations to construct the Azo cross-linked liquid crystalline polymers networks model that satisfies the structural and thermodynamic properties of the full-atomistic reference [248]. Employing computer simulation techniques, Guskova et al have analyzed the noncovalent interactions between the Azo arms in benzene-1,3,5-tricarboxamide columns [249,250]. Furthermore, Kudernac et al used all-atom MD method to simulate the effect of trans-cis isomerization on the self-assembled nanotube formed by angular monomers containing Azo tails [251].…”
Section: Theoretical Calculations and Simulationsmentioning
confidence: 99%
“…The formation and the properties of supramolecular aggregates built from such threearm azobenzene stars have been studied in various experimental [37][38][39]45] and theoretical works [46,47]. It was found that these molecules assemble into different morphologies depending on the solvent [37,38].…”
Section: Introductionmentioning
confidence: 99%